Factor structure of the readiness of highly skilled freestyle skiers (mogul) - Zdanovich, O.S.; Zebzeev, Vl.V.; Ilyukhin, I.A.; Moiseeva, N.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the factor structure of elite freestyle skiers' preparedness using the example of the mogul discipline. Methods and structure of the study. To achieve this goal, the method of factor analysis was used, which was implemented using the IBM SPSS Statistics computer program. The study involved highly qualified freestyle skiers (men), members of the Russian national mogul team (n=36) aged 20-25 years. 9 factors were identified in the structure of the mogulists: special morphology, general morphology, strength, anaerobic abilities, coordination, effectiveness of the cardiovascular system, speed and strength abilities, athletic and technical fitness and technique of downhill skiing. Results and conclusions. The results of the study revealed that the factorial structure of the training of highly qualified mogulists has a pronounced morphological orientation. The greatest impact on athletic performance is exerted by special and general morphology, including indicators of muscle and fat components, height and body weight. These parameters determine the effectiveness of an athlete's movements on the track and the level of his functional fitness to the extreme conditions of competitive activity. Factors of strength, anaerobic capacity, and coordination also make a significant but less pronounced contribution to performance. The data obtained confirm the need to take into account morphological characteristics when planning a training process aimed at developing optimal ratios of mass, strength and technique in moguls. Thus, the presented factor structure makes it possible to specify the key areas of training for elite freestyle skiers and serves as the basis for improving scientific and methodological support in this sport.